Faktor - Faktor yang Mempengaruhi Loyalitas Tamu - Belinda, Belinda; Rahardjo, Joko S Dwi (NIAGARA Scientific Journal, 2024)
This scientific work aims to analyze the factors that influence hotel guest loyalty, with a focus on the competitive hotel industry. This study covers various relevant aspects such as service quality, hotel facilities, pricing, user experience, hotel reputation, and guest experience and reputation management. The research methods used include literature studies and analysis of key factors that have been researched and proven to influence guest satisfaction and loyalty. The results of this analysis show that high service quality, adequate facilities, appropriate pricing according to the value provided, as well as effective management of guest experience and reputation greatly contribute to increasing the level of guest satisfaction and loyalty. This research also highlights the importance of using technology in managing the guest experience, regularly monitoring feedback, and adapting to changing market trends to maintain hotel competitiveness in an increasingly competitive market. The practical implication of this scientific work is that hotels can improve their strategies in managing various factors that influence guest loyalty to achieve competitive advantage and build fruitful long-term relationships with their guests. In conclusion, continuous efforts to improve service quality, facilities, price management and user experience are the keys to success for hotels in creating a satisfying stay experience and building strong loyalty with their guests.